Protective Effects of Lycium ruthenicum Murray against Acute Alcoholic Liver Disease in Mice via the Nrf2/HO-1/NF-κB Signaling Pathway - Niantong Xia; Zimian Ding; Mingran Dong; Shuyang Li; Jia Liu; Hongwei Xue; Zhigang Wang; Juan Lu; Xi Chen (MDPI AG, 2024)
Acute alcoholic liver disease (ALD) resulting from short-term heavy alcohol consumption has become a global health concern. Moreover, anthocyanins have attracted much attention for their ability to prevent oxidation and inflammation. The present work evaluates the protective effects of Lycium ruthenicum Murray (LRM) against ALD and explores the possible underlying mechanism involved. The total anthocyanin content in LRM was 43.64 ± 9.28 Pt g/100 g dry weight. Mice were orally administered 50, 125, or 375 mg LRM/kg body weight (BW) for 21 days. On days 18-21, mice were orally administered 15 mL of ethanol/kg BW. Markers of liver damage, oxidative stress, and inflammation were examined. Furthermore, the modulatory effect of LRM on Nrf2/HO-1/NF-κB pathway molecules was evaluated through quantitative reverse transcription polymerase chain reaction (RT‒qPCR) and immunohistochemistry analyses. The difference between the groups indicated that LRM improved liver histopathology and the liver index, decreased aspartate transaminase, alanine transaminase, malondialdehyde, reactive oxygen species, IL-6, TNF-α, and IL-1β expression, but elevated superoxide dismutase, catalase, and glutathione-s-transferase levels. Moreover, LRM upregulated Nrf2 and Ho-1 but downregulated Nf-κb and Tnf-α genes at the transcript level. In summary, LRM alleviated ethanol-induced ALD in mice by reducing oxidative damage and associated inflammatory responses. LRM protects against ALD by reducing damage factors and enhancing defense factors, especially via the Nrf2/HO-1/NF-κB pathway. Thus, LRM has application potential in ALD prophylaxis and treatment.